Analytical formulation of the stiffness method for 2d reticular structures using green functions (2020)
Green functions (F.G.) are defined as the response of a medium to a unit point load and are widely used to solve boundary value problems. Unfortunately, in structural analysis, its use is limited and they are only used indirectly and with another name in the calculation of influence lines and in the formulation of the virtual work method. This article presents the Green functions stiffness method, which is a novel methodology to obtain the analytical or exact response of two dimensional frames, which mixes the stiffnes method and the Green functions, the latter used for the calculation of displacement fields. In particular, the formulation will be carried out for bar elements (subjected to axial force), beam elements (subjected to shear force and bending moment), beam over flexible foundation elements (subjected to shear force and bending moment) and two dimensional frames (subjected to axial force, cutting force and bending moment). This formulation has as its main property that it can be used to compute the analytic reponse for any external load distribution and minimizes the number of elements to be used in discretizations. In addition, the equivalence of this formulation with that obtained by an “exact” implementation of the finite element method is presented. © 2020, Scipedia S.L. All rights reserved.